Selected aspects of patient communication and occupational burnout among nurses working during the COVID-19 pandemic - Mazur, Joanna; Kozakiewicz, Alicja; Białorudzki, Maciej; Izdebski, Zbigniew (Nursing in the 21st Century, 2023)
SELECTED ASPECTS OF PATIENT COMMUNICATION AND OCCUPATIONAL BURNOUT AMONG NURSES WORKING DURING THE COVID-19 PANDEMICAim. The purpose of the study was to assess how perceived verbal and non-verbal communication, occupational burnout, age, having children and satisfaction with job performance interact with communication with patients among nurses during the COVID-19 pandemic.Material and methods. Total number of 1187 female nurses, who declared that they work with patients on a daily basis, were included in the analyses. The mean age of the respondents was 50.4 (SD = 10.1) years. The study used the author’s questions relating to perceived verbal and non-verbal communication, as well as the HPCSS-12 (Health Professionals Communication Scale) and BAT-12 (Burnout Assessment Tool) scales.Results. In the linear regression model perceived importance of non-verbal communication (b = 0.135; p